Axillary web syndrome in a pediatric patient with no history of surgery: A case report - Jacob Denton; Kareem W. Shehab (Journal of Orthopaedic Reports)
Introduction: axillary web syndrome is typically a consequence of axillary lymph node dissection and is rarely arises from trauma or physical exertion. A pediatric case has not been previously described. Case report: A 15-year-old with prior uncomplicated pulmonary coccidioidomycosis developed a tender, palpable cord originating in the right axilla extending along the medial biceps after a session of resistance weight training. There was no prior history of surgery or malignancy. She did not have axillary adenopathy and had no signs of relapsed coccidioidal infection. She experienced near-resolution with physical therapy. Discussion: This is the first known pediatric case of axillary web syndrome, which should be included in the differential diagnosis when approaching pediatric patients with compatible signs and symptoms in the setting of resistance training.